Polysaccharide degradation by lytic polysaccharide monooxygenases. (December 2019) - Forsberg, Zarah; Sørlie, Morten; Petrović, Dejan; Courtade, Gaston; Aachmann, Finn L; Vaaje-Kolstad, Gustav; Bissaro, Bastien; Røhr, Åsmund K; Eijsink, Vincent GH
Highlights: Lytic polysaccharide monooxygenases (LPMOs) are abundant in nature and of great biotechnological interest. Substrate binding affects the catalytic competence of the unique mono-copper catalytic center in LPMOs. LPMOs are sensitive to autocatalytic inactivation, in particular in the absence of a proper substrate. The recently discovered peroxygenase activity sheds new light on LPMO functionality in nature and in industrial bioprocessing. Abstract : The discovery of oxidative cleavage of glycosidic bonds by enzymes currently known as lytic polysaccharide monooxygenases (LPMOs) has had a major impact on our current understanding of the enzymatic conversion of recalcitrant polysaccharides such as chitin and cellulose. The number of LPMO sequence families keeps expanding and novel substrate specificities and biological functionalities are being discovered. The catalytic mechanism of these LPMOs remains somewhat enigmatic. Recently, novel insights have been obtained from studies of enzyme–substrate complexes by X-ray crystallography, EPR, NMR, and modeling. Furthermore, it has been shown that LPMOs may carry out peroxygenase reactions, at much higher rates than monooxygenase reactions, which affects our understanding and exploitation of these powerful enzymes.